Aggregate shape effect on fracture and breakage of cementitious granular materials. (15th April 2022) - Jiang, Sheng; Shen, Luming
Highlights: Aggregate shape effect on CGM stiffness increases with strength or rate. The critical strain energy of CGMs is revealed to be aggregate shape independent. The coupled evolution of fragment size and shape is characterised microscopically. Abstract: To assess the aggregate shape influences on the cementitious granular material fracture and breakage behaviors, mortar samples containing two types of aggregates with same material but different shapes, namely, irregular glass particles and rounded glass particles, are compressed under quasi-static to high strain rate (1000–3500 s −1 ) loadings. Experimental results reveal that the extent of aggregate shape effect on the mortar stiffness is significantly enhanced with the increase of strain rate or cement strength. Although the critical strain energy is discovered to be aggregate shape independent, different microscopic fracture evolutions induced by the aggregate shape influences still exist and are effectively reflected by the corresponding coupled evolution of fragment size and shape. Meanwhile, the fracture locality preference within the aggregate particles is also validated by the associated microscopic evidence. This study sheds light on the future high strength granular composite material design, in particularly, upon high strain rates. Graphical abstract: Image, graphical abstract